Family Child Care Program Closure in Alabama During the COVID-19 Pandemic - Alison Hooper; JoonHo Lee; Claire Schweiker (SAGE Publishing, 2023)
Family child care (FCC) is uniquely positioned to address challenges with insufficient early care and education supply and access in the United States. FCC programs were steadily declining before COVID-19, and many child care programs, both center- and home-based, were at risk of closure early in the pandemic. This study examines closure among Alabama FCC providers during COVID-19. Specifically, we examine the timing and predictors of FCC providers' closure using discrete time-hazard modeling. We analyze administrative data for the 788 FCC programs licensed in March 2020. Over the following 28 months, FCC closure risk was closely linked with COVID-19 disease spread trends. Providers who participated in child care subsidy or national accreditation had lower closure risk than those who did not. The protective effects of subsidy participation were amplified in lower-opportunity communities. Results have implications for mitigating FCC decline and identifying resources to support FCC providers' continued operation.